Magnetic Resonance Imaging-Guided Prostate Biopsy: Institutional Analysis and Systematic Review - Polanec, S. H.; Helbich, T. H.; Margreiter, M.; Klingler, H. C.; Kubin, K.; Susani, M.; Pinker-Domenig, K.; Brader, P. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
Objectives: To evaluate the detection rate of prostate cancer (PCa) after magnetic resonance-guided biopsy (MRGB); to monitor the patient cohort with negative MRGB results and to compare our own results with other reports in the current literature.Materials and Methods: A group of 41 patients was included in this IRB-approved study and subjected to combined MRI and MRGB. MRGB was performed in a closed 1.5 T MR unit and the needle was inserted rectally. The follow-up period ranged between 12 and 62 months (mean 3.1 years). To compare the results with the literature, a systematic literature search was performed. Eighteen publications were evaluated.Results: The cancer-suspicious regions were punctured successfully in all cases. PCa was detected in eleven patients (26.9 %) who were all clinically significant. MRGB showed a benign histology in the remaining 30 patients. In the follow-up (mean 3.1 years) of patients with benign histology, no new PCa was diagnosed. The missed cancer rate during follow-up was 0.0 % in our study.Conclusion: MRGB is effective for the detection of clinically significant cancer, and this is in accordance with the recent literature. In the follow-up of patients with benign histology, no new PCa was discovered. Although the probability of developing PCa after negative MRGB is very low, active surveillance is reasonable.Key points:• MRGB is a reliable and safe method for the detection of PCa.• In the follow-up of patients with benign biopsy-results, no new PCa was detected.• Probability of detecting a cancer after negative MRGB is low.Citation Format:• Polanec SH, Helbich TH, Margreiter M et al. Magnetic Resonance Imaging-Guided Prostate Biopsy: Institutional Analysis and Systematic Review. Fortschr Röntgenstr 2014; 186: 501 – 507
Keywords: prostate; biopsy; interventional MR